PENGENDALIAN KUALITAS KEMASAN OBAT PADA PERUSAHAAN FARMASI MENGGUNAKAN METODE SIX SIGMA, POKA YOKE DAN KAIZEN - Jessica; Salomon, Lithrone Laricha; Ahmad (Jurnal Ilmiah Teknik Industri, 2025)
This study was conducted at a pharmaceutical manufacturing company, focusing on the blistering process of capsule products. Quality control issues were identified, particularly defects that do not meet company standards. The objective of this research is to identify the root causes of defects and propose improvements using the Poka Yoke and Kaizen methods. The study is limited to defects found in capsules that have passed the blistering stage, including crushed capsules, dirt contamination, misprinted expiration dates, and empty capsules. The capsules used in the study already meet company standards before processing. The analysis applies the Six Sigma methodology with the DMAIC approach (Define, Measure, Analyze, Improve, Control). Results from January 2024 to March 2025 show a DPMO value of 9100.625 and a sigma level of 3.86. The Pareto diagram indicates that the most dominant defects are crushed capsules (35.8%) and dirty capsules (30%). Based on FMEA analysis, the highest RPN values are caused by capsule misalignment in the blister machine (for crushed defects) and powder residue sticking to the sealing area (for dirty defects). Improvements are proposed using Poka Yoke techniques and continuous improvement through Kaizen, specifically applying the 5M and 5S principles.